RANCANG BANGUN SISTEM INFORMASI PEMBAYARAN GAJI KARYAWAN PEKERJA HARIAN LEPAS (PHL) PADA PERUSAHAAN PERKEBUNAN SAWIT (PT X) - Parhusip, Jadiaman (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
Computer-based information technology is one way to process the data into an information quickly and accurately. At this time the computer is also one form of the development of technology that can be used as a means to get information. Computers also play an important role in information technology that we need without the limitations of space and time. Computer-based information technologyis one way to process the data and make the information quickly and accurately at the present time.Perusahaan Perkebunan Sawit (PT X) is a subsidiary of the Bakrie Group is located at KM 11 Nanga Bulik Lamandau District. At Perusahaan Perkebunan Sawit (PT X) employees divided into two permanent employees and casual workers. There are 381 PHL (Daily Worker Release) consists of 9 people porters, 16 foremen, 261employees daily, and 95 harvesters.Payment of salaries and equipment is computed by the central office. For permanent employee salary payment system done once a month or within 26 working days. As for the non-permanent employees salary will be paid every 15 days of work which is calculated based on the amount of work daily. So in one month salary payment PHL there were two periods. Currently for rate (base salary) one working day is Rp.47.652, 00 -. One working day is over 7 hours. For payment beyond the rate is calculated based on premiums earned.